Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.4143/crt.2018.157
|View full text |Cite
|
Sign up to set email alerts
|

Founder Mutations for Early Onset Melanoma as Revealed by Whole Exome Sequencing Suggests That This is Not Associated with the Increasing Incidence of Melanoma in Poland

Abstract: Although most of the changes seemed to be neutral we could not exclude an association between variants in VRK1, CREB3L3, EXO5 and STK33 with melanoma risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Te fourth biomarker is CREB3L3, a member of the basic leucine zipper family and the AMP-dependent transcription factor family. It can link to acute infammatory response and hepatocellular carcinoma [47]. Dewaele et al illustrated that EWSR1-CREB3L3 gene fusion is associated with a mesenteric sclerosing epithelioid fbrosarcoma [48].…”
Section: Discussionmentioning
confidence: 99%
“…Te fourth biomarker is CREB3L3, a member of the basic leucine zipper family and the AMP-dependent transcription factor family. It can link to acute infammatory response and hepatocellular carcinoma [47]. Dewaele et al illustrated that EWSR1-CREB3L3 gene fusion is associated with a mesenteric sclerosing epithelioid fbrosarcoma [48].…”
Section: Discussionmentioning
confidence: 99%
“…CABLES1 presented with only one highly ranked candidate and is generally not associated with UM or CM apart from containing a potential driver mutation site. 28 We obtained three topranked peptides from PMEL, another pigmentation gene and CM antigen, which is considered a highly ranked candidate biomarker in UM. 29 Finally, the gene OCA2 produced two top-ranked peptides for the allele A*02:01.…”
Section: Ranking Of Antigens Based On Their Importance In a Cancertar...mentioning
confidence: 99%
“…The expression of STK33 in pancreatic cancer, lung cancer, and liver cancer was signi cantly higher than that in corresponding non-cancerous tissues, indicating that the high expression of STK33 is closely related to the occurrence and development of pancreatic cancer, lung cancer and liver cancer (12)(13)(14). In the early stage of familial hereditary melanoma, the whole exon sequencing showed that STK33 was one of the 20 gene mutations, which suggested that STK33 played a role in its occurrence (15). Studies on lung cancer showed that the mRNA and protein expression of STK33 in lung adenocarcinoma, squamous cell carcinoma and small cell carcinoma were signi cantly higher than those in normal tissues, and the expression of STK33 in small cell carcinoma was higher than that in adenocarcinoma and squamous cell carcinoma (13,16).…”
Section: Introductionmentioning
confidence: 98%